Method and implementation to overlay radar image on the electronic chart - Sediono, Wahju; Dharmawan, Tjen Syerwin; Lestari, Andrian Andaya (Akademi Angkatan Udara, 2010)
Electronic navigation becomes increasingly more common, particularly onboard commercial vessels. As one of important elements in the electronic navigation, the electronic chart has introduced a new level of performance to navigation such as Electronic Chart Display and Information System (ECDIS). As a completely new and interactive navigation information system, it has an undisputable capability for displaying all necessary chart and navigation-related information required for the safe operation of a vessel. However, despite its many advantages, an electronic chart does not present the dynamic real-time situation within a certain area or cell of the chart. To overcome this problem many ships are equipped with additional marine radars to monitor the real situation around their actual positions. Current trends show that there is an increasing demand to complement the electronic chart with available radar image. This paper describes a method and implementation to overlay radar image into the existing electronic chart.